Effectiveness of Bioinsecticide Bacillus thuringiensisFormulation Against Cocoa Pod Borer in Field Condition - Rein E Senewe; F.X Wagiman; Soekadar Wiryadiputra (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2013)
Field trial of Bt insecticide formulation with a code of formulation-A +1WP against cocoa pod borer (CPB) (Conopomorpha cramerella) has been conducted at the heavily infested cocoa area in Holo village, Amahai sub district, Central Maluku regency. Formulation-B 2.5 WP as a commercial Bt insecticide which has been distributed widely in the market was used as a comparison Bt insecticide. The results of the trial revealed that compared with untreated treatment, Bt insecticide formulation-A +1WP significantly reduced infestation of CPB, CPB population, and yield losses of dry cocoa bean caused by CPB. At the same concentration (2.5 g/L), the effectiveness of formulation-A +1WP was not significantly different with formulation-B 2.5WP. In the case of production increase, at the same concentration (2.5 g/L) formulation-A +1WP caused higher yield than formulation-B 2.5WP, i.e. 39.9% compared with 35.1%, respectively. Both Bt insecticide formulations tried did not caused phytotoxic against cocoa plant. It is recommended that controling of CPB should use concentration of 2.5 g/L Bt insecticide formulation/L of water, and should be applied at around early morning until 09.00 AM and / or at the afternoon after 15.00 PM. Spraying targets should be cocoa pods at the length of less than 8.0 cm which is not laid eggs of CPB yet. Key words: Cocoa, cocoa pod borer, Conopomorpha cramerella, control, effectiveness, microbial insecticide, Bacillus thuringiensis